Patriotism, taxation and international mobility - Salmai Qari; Kai A. Konrad; Benny Geys (Institute for the Study of Labor (IZA), 2009)
For patriotic citizens, living in their native country is intrinsically preferable compared to living in the diaspora. In this paper, we analyze the implications of such a patriotic lock-in in a world with international migration and redistributive taxation. In a formal model of redistribution with international migration and fiscal competition we derive the main hypothesis: that countries with a more patriotic population should have higher redistributive taxes. Using ISSP survey data and combining them with OECD taxation data, we find robust evidence suggesting that a) higher patriotism is associated with higher tax burdens, and b) this relation is stronger for the upper-middle range of the income distribution.
urn:nbn:de:101:1-20090513177
Keywords: H20; H73; 330; Patriotism; international mobility; taxation; redistribution; fiscal competition; Ethnopsychologie; Gesellschaftliches Bewusstsein; Internationale Wanderung; Steuersystem; Steuerwirkung; Einkommensumverteilung; OECD-Staaten